Mind over matter: consistency monitoring and domain-specific learning - Bascandziev, Igor; Abutto, Adani; Walker, Caren M.; Bonawitz, Elizabeth (Frontiers in Developmental Psychology, 2025)
IntroductionChildren's naïve understanding of the physical world is permeated with inconsistencies among beliefs. For example, young children who believe that air does not occupy space also believe that balloons are filled up with air. Here, we asked if an ability to explicitly notice inconsistencies among statements is associated with a more mature understanding of the physical world.MethodWe tested 100 children who received a Physics Interview, a battery of Executive Functioning measures, a Cognitive Reflection measure, and a Consistency Monitoring measure.Results and discussionWe found that Consistency Monitoring is associated with Physics Understanding, even when controlling for Age, Executive Functioning, and Cognitive Reflection. This finding highlights the importance of explicit consistency monitoring skills in the accumulation and expression of domain-specific understanding of the physical world, and it suggests future avenues for development and research of educational interventions that take into account the role of consistency monitoring skills in science learning.